Comparison of Steam Explosion and Ferric Chloride Solution Pretreatment of Corn Stover: Composition Content, Structural and Enzymatic Hydrolysis - Zeng, G.M.; Wang, Y.L.; Zhang, M.L.; Zheng, Y.X.; Xing, J.; Ma, Y.F.; Xu, H.J. (Asian Journal of Chemistry, 2012)
The efficiency of two lignocellulose pretreatment technologies, steam explosion and ferric chloride solution pretreatment, are compared in terms of composition, structural and enzymatic efficiency with corn stover. Ferric chloride solution pretreatment could easily remove almost all of the hemicelluloses and gain high enzymatic hydrolysis compared with steam explosion, but they both have no effect on delignification and reduced cellulose crystalline. Pretreated material was investigated by X-ray diffraction, scanning electron microscopy and Fourier transform infrared spectroscopy. These results suggested that ferric chloride solution pretreatment may own huge advantages compared to the steam explosion pretreatment process for corn stover. However, the recovery of the ferric chloride solution should also be paid more attention.